Harnessing Kinship for Family Business Development in Rural Tourism: Insights from Indonesia - Irawati, Ira; Hermawati, Rina; Munajat, MD Enjat; Saefullah, Kurniawan; Ismail, Hairul Nizam (European Journal of Family Business, 2024)
The tourism sector in Indonesia offers a significant platform for family businesses to drive economic growth, particularly in rural areas. In such settings, these enterprises often involve not only nuclear families but also extended families connected through kinship networks. This study examines the role of kinship in the development of family businesses within the Ciletuh Palabuhanratu UNESCO Global Geopark, Indonesia. Focusing on family enterprises in Ciwaru village, the research aims to explore how kinship relationships contribute to business sustainability and growth. Utilizing qualitative methods and a case study approach, the study applies concepts of family business, kinship, and inheritance systems. Findings reveal that kinship serves as a critical resource, providing labor, facilitating business promotion, ensuring generational continuity, and broadening business activities. These networks foster cooperation, trust, and shared experience, enabling family businesses to thrive. Furthermore, the growth of these enterprises has played a pivotal role in addressing poverty in Ciwaru village, highlighting the socio-economic impact of kinship-based family businesses.